1992
DOI: 10.1002/jlb.51.6.617
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity in the circulating neutrophil pool: studies on subpopulations separated by continuous flow electrophoresis

Abstract: Isolated blood neutrophils from healthy individuals have been separated by continuous flow electrophoresis (CFE) as a Gaussian-shaped profile extending over 12-15 fractions, on the basis of differences in cell surface electrical charge. The fractions were pooled into three or four subpopulations; the mean electrophoretic mobilities of the least and most electronegative cells were 0.96 and 1.22 microns/sec/V/cm, respectively. Each pool of neutrophils was analyzed for functional and biochemical differences. Expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

1994
1994
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 20 publications
2
8
0
Order By: Relevance
“…Priming of these cells with PAF did not enhance their generation of 02production by FMLP, which was in contrast to the neutrophils with a high net negative surface charge, which exhibited significant increases in responsiveness following PAF priming. These findings add support to the concept that there is functional and metabolic heterogeneity within neutrophils,917 and that the magnitude techniques (continuous flow electrophoresis and partitioning in two phase aqueous polymer systems), our earlier studies showed that blood neutrophils are heterogeneous with respect to cell surface membrane electrokinetic properties and functional responsiveness.3 14 Our previous work also demonstrated that neutrophils of a low electrophoretic mobility were increased in the blood and particularly in the synovial fluid of RA patients,9 1 and that immune complexes reduced the surface charge of normal blood neutrophils.30 In the present study, rheumatoid synovial fluid neutrophils separated by CFE were found to be of a consistently lower electrophoretic mobility than autologous blood neutrophils. Neutrophils within rheumatoid joints are reported to be activated as judged by their 02produc-tion28 29 and receptor expression.…”
Section: Discussionsupporting
confidence: 70%
“…Priming of these cells with PAF did not enhance their generation of 02production by FMLP, which was in contrast to the neutrophils with a high net negative surface charge, which exhibited significant increases in responsiveness following PAF priming. These findings add support to the concept that there is functional and metabolic heterogeneity within neutrophils,917 and that the magnitude techniques (continuous flow electrophoresis and partitioning in two phase aqueous polymer systems), our earlier studies showed that blood neutrophils are heterogeneous with respect to cell surface membrane electrokinetic properties and functional responsiveness.3 14 Our previous work also demonstrated that neutrophils of a low electrophoretic mobility were increased in the blood and particularly in the synovial fluid of RA patients,9 1 and that immune complexes reduced the surface charge of normal blood neutrophils.30 In the present study, rheumatoid synovial fluid neutrophils separated by CFE were found to be of a consistently lower electrophoretic mobility than autologous blood neutrophils. Neutrophils within rheumatoid joints are reported to be activated as judged by their 02produc-tion28 29 and receptor expression.…”
Section: Discussionsupporting
confidence: 70%
“…A membrane receptor for elastase, another azurophil granule enzyme closely related to PR3, has indeed be reported on PMN [28]. Furthermore, the highly basic PR3 molecule could bind to negatively charged components of the cell glycocalyx and charge heterogeneities have been described in the neutrophil pool [21]. The molecular basis of the heterogeneity among mature neutrophils is not known from this study but the stability, for one given subject, of the proportion of this PMN subset suggests that it may be under genetic control.…”
Section: Discussionmentioning
confidence: 94%
“…Various techniques of cell fractionation by density centrifugation or flow electrophoresis revealed physicochemical and functional heterogeneity in the circulating neutrophil pool [19][20][21]. Some of these variations concerned azurophil or specific granule components defining subpopulations of PMN with differences in myeloperoxidase or lactoferrin activity [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…Besides a distribution of buoyant densities, other studies have shown functional heterogeneity within the circulating neutrophil pool of healthy humans 11,12,13 . For instance, in the studies of Eggleton et al.…”
Section: Density Is a Spectrum In Neutrophilsmentioning
confidence: 99%